Refugeeness, Sexuality, and Gender: Spatialized Lived Experiences of Intersectionality by Queer Asylum Seekers and Refugees in Paris - Chossière, Florent (Frontiers in Human Dynamics, 2021)
In the last years, asylum claims based on sexual orientation and/or gender identity (SOGI) have received increased attention within migration and queer studies. Mostly focusing on the refugee status determination process, these works have emphasized how the expectations of asylum institutions about “genuine queer refugees” lead to excluding many applicants from SOGI asylum. In this paper, I aim at shifting the analysis perspective from the legal categorization process to the impacts of everyday experienced categories of “asylum seeker” or “refugees” on queer migrants in the Parisian area. Using a three-year long ethnographic fieldwork, completed through interviews with queer asylum seekers and refugees, I investigate how refugeeness, understood as the objective and subjective effects of migration and asylum policies on individuals, contributes to shaping lived experiences of sexual and gender minorities in France. By drawing attention to the ways that the multiple power relationships queer asylum seekers and refugees have to face are spatially grounded, I discuss how an intersectional understanding of sexuality, gender, and refugeeness allows us to emphasize the role played by migration status in the negotiation of hetero- and cisnormativity. I also argue that far from remaining passive toward the categorization process they are subjected to, queer asylum seekers and refugees strategically appropriate the administrative categories with which they are associated. Such an analysis of lived experiences of queer asylum seekers and refugees in the country of arrival thus highlights the complex reshaping of social location caused by migration.